2014
DOI: 10.1080/13611267.2014.983326
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Correlates of Supportive Peer Mentoring: A Mixed Methods Study

Abstract: In this mixed methods study, we employed thematic analysis (TA) to examine peer mentors' perceptions of benefits, challenges, and roles they experienced as mentors, as well as benefits and challenges experienced by first-year college students. We also utilized quantitative student ratings to classify mentors as highly, moderately, or minimally supportive in order to determine whether any subthemes from the TA appeared more or less frequently across the three groups. Highly supportive mentors reported greater c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…Indeed, these skills and outcomes are integral to a positive peer mentoring experience, both for the mentor and mentee, which is why we believe there is utility to examining attachment in the context of a peer mentor program. Further, recent qualitative findings from our research group suggest that even in a peer mentoring program with an academic focus, 56% of mentors reported serving as a trusted friend or confidante to their mentees (Holt & Lopez, 2014), which is consonant with Gershenfeld's (2014) finding that 55% of the collegiate mentoring programs reported that their mentors provided psychosocial or emotional support. Without question, more research on peer mentor attachment style and its associated outcomes is needed to establish whether our findings are generalizable to peer mentors at other institutions of higher education, particularly mentors in dissimilar environments, such as public institutions or community colleges.…”
Section: Limitations and Future Directionssupporting
confidence: 57%
“…Indeed, these skills and outcomes are integral to a positive peer mentoring experience, both for the mentor and mentee, which is why we believe there is utility to examining attachment in the context of a peer mentor program. Further, recent qualitative findings from our research group suggest that even in a peer mentoring program with an academic focus, 56% of mentors reported serving as a trusted friend or confidante to their mentees (Holt & Lopez, 2014), which is consonant with Gershenfeld's (2014) finding that 55% of the collegiate mentoring programs reported that their mentors provided psychosocial or emotional support. Without question, more research on peer mentor attachment style and its associated outcomes is needed to establish whether our findings are generalizable to peer mentors at other institutions of higher education, particularly mentors in dissimilar environments, such as public institutions or community colleges.…”
Section: Limitations and Future Directionssupporting
confidence: 57%
“…The importance of trust, open communication, and connectedness to mentees has been shown to be an essential component for effective peer mentoring practices (Holt & Lopez 2014;James et al 2014;Willis et al 2012). The young mentors recognized that relationship could not be built with vulnerable mentees if these elements of a relationship were not developed.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of trust, open communication, and connectedness to mentees has been shown to be an essential component for effective peer mentoring practices (Holt & Lopez ; James et al . ; Willis et al .…”
Section: Discussionmentioning
confidence: 99%
“…The mentoring literature largely focuses on the experiences and outcomes of mentoring partnerships (Crisp et al , 2017). Measurable direct and indirect outcomes for both the mentor and mentee noted in the literature include a strong emphasis on mentor outcomes (Engler, 2015; Holt and Lopez, 2014; North-Samardzic and Cohen, 2016) and impact on mentees participating in the partnerships (Baier et al , 2016; Crisp, 2009). Crisp and Cruz (2009) argued participating in college student mentoring programs yielded four outcomes: psychological and emotional support, degree and career support, academic subject knowledge support and role modeling.…”
Section: Literature Reviewmentioning
confidence: 99%